National Health Insurance on Household Out-of-pocket Health Expenses in Indonesia - Ira Yusnita Wijayati; Dwini Handayani (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
BPJS Kesehatan is expected to increase access to fair and high-quality health care for all citizens and provide financial risk protection. Our study aims to examine the impact of BPJS Kesehatan’s implementation as national health insurance (NHI) on household out-of-pocket expenses. Our study used a difference in differences (DID) regression model that was applied to repeated cross-section data from the National Socio-Economic Survey (Susenas) between 2013-2014 and 2019-2020. Propensity-score matching (PSM) is used to provide covariate balance in the regression model data. Illnesses that are represented by health conditions and treatment options (self-medication, outpatient, inpatient) are determining factors of out-of-pocket expenses. Our finding, the implementation of BPJS Kesehatan resulted in a 26.0% increase in out-of-pocket expenses. Its main reason is an increase in public health awareness, as indicated by the increased number of visits to health facilities. However, the increase in out-of-pocket expenses suggests that the usage of BPJS Kesehatan is not optimal. To optimize its function as financial protection, improvements must be made to the mechanism and system policies.